Mapping gray matter changes in anorexia nervosa: a functional connectivity network approach - Yang, HuCheng; Wang, Shu; Li, HuaLiang; Gu, SiYu; Zhang, FengMei; Wang, HongHui; Dai, ZhenYu; Pan, PingLei (Frontiers in Nutrition, 2025)
BackgroundStudies using voxel-based morphometry (VBM) have shown considerable variability in gray matter (GM) changes in anorexia nervosa (AN). However, it remains unclear whether these changes converge on common brain networks underlying the disorder.MethodsA systematic review was conducted using the PubMed, Embase, and Web of Science databases to identify studies on whole-brain GM alterations in AN published up to October 10, 2024. The Human Connectome Project (HCP) dataset (n = 1,093) and functional connectivity network mapping (FCNM) approach to identify common brain networks associated with alterations in AN.ResultsA total of 26 studies involving 667 individuals with AN and 659 healthy controls (HC) were included in this study. Combining the HCP dataset and the FCNM technique, we demonstrated that the disrupted neural networks primarily involved the auditory network, ventral default mode network (DMN), dorsal DMN, and sensorimotor network (SMN). Subgroup analyses further revealed differences in the affected neural networks across specific subgroups, including females-only, adolescents, and adults.ConclusionThe heterogeneous GM alterations in AN can be attributed to common abnormalities within the auditory network, DMN, and SMN. These disruptions are linked to distorted body image, impaired emotional regulation, and disrupted sensory-motor integration in AN. The FCNM technique provides a unified network-level understanding of the neurobiological mechanisms underlying AN, offering insights for targeted therapeutic strategies.